Believing After Darwin: the Debates of the Metaphysical Society (1869–1880) - Catherine Hajdenko-Marshall (Cahiers Victoriens et Edouardiens)
The Metaphysical Society is often referred to as a rather discreet debating society but the role it played in questioning the ideas pertaining to science and faith in the second half of the nineteenth century has rarely been properly discussed. The members of the Metaphysical Society were all well-known members of the Victorian elite who held a variety of religious and political views. They produced ninety-five papers over a period of eleven years which have never been analysed together as a coherent set. They attempted to find a way of believing after the discoveries of Charles Darwin as if religion had been challenged by science. In fact, what the papers reveal is that science and the methods of scientists could be used to explain religion and religious faith and that the opposition between science and faith was not as important as expected. The present article aims to show that the questions they asked are still very relevant to twenty-first century citizens—even in the diversity of the religious views presented and the methodology adopted. As such, the Metaphysical Society remains an interesting experiment, which failed, but which still has a lot to teach us.